Interaction Analysis and Contribution of Total Mudharabah Deposits in Sharia Banking in Indonesia 2015-2020 Period - Saparuddin Siregar; Tuti Anggraini; Asmiwarti Asmiwarti (Budapest International Research and Critics University, 2022)
This study aims to determine the interaction and contribution of Total Mudharabah Deposits, GDP, BI Rate, Inflation and Profit Sharing in Islamic Banking in Indonesia. The research approach used is a quantitative research approach with the Vector Auto Regression (VAR) analysis technique of the VECM model supported by Stationarity Test, Model Stability Test, Optimal Lag Length Test, Granger Causality Test, Cointegration Test, Impulse Response Function Test, and Variance Decomposition Test. assisted by Software Eviews 9. This study uses a sample from 2015 to 2020. The results show that there is a causal relationship between GDP and Mudharabah Deposits, Profit Sharing on Mudharabah Deposits, Inflation on BI Rate, BI Rate on Profit Sharing. In the long-term relationship, BI Rate and Inflation have a positive effect on Mudharabah Deposits, while GDP and Profit Sharing have a negative effect on Mudharabah Deposits. In the short term, the GDP variable has a positive and significant effect on inflation. Based on the Impulse Response Function (IRF) analysis, all variables in the short term have a stable response and experience few shocks and based on the Forecast Error Variance Decomposition (FEVD) analysis, the GDP variable is the variable that has the largest response and the largest composition compared to other variables.